Elevated blood pressure and illness beliefs: a cross-sectional study of emergency department patients in Jamaica - Wilson, Taneisha T. (Int J Emerg Med, 2018)
BACKGROUND: Elevated blood pressure (BP) is common among emergency department (ED) patients. While some data exist on the association between ED BP and hypertension (HTN) in the USA, little is known about this relationship in Afro-Caribbean nations. The aim of the study was to evaluate the relationship between elevated systolic BP in the ED and a previous diagnosis of HTN, accounting for potential factors that could contribute to poor HTN control among those with a previous diagnosis: socioeconomic status, health-seeking behavior, underlying HTN illness beliefs, medication adherence, and perceived adherence self-efficacy. METHODS: This was a cross-sectional survey over 6 weeks, from November 19 through December 30, 2014. Those surveyed were non-critically ill or injured adult ED patients (≥ 18 years) presenting to an Afro-Caribbean hospital. Descriptive statistics were derived for study patients as a whole, by HTN history and by presenting BP subgroup (with systolic BP ≥ 140 mmHg considered elevated). Data between groups were compared using chi-square and t tests, where appropriate. RESULTS: A total of 307 patients were included: 145 (47.2%) had a prior history of HTN, 126 (41.4%) had elevated BP, and 89 (61.4%) of those presenting with elevated blood pressure had a previous diagnosis of HTN. Those with less formal education were significantly more likely to present with elevated BP (52.1 vs. 28.8% for those with some high school and 19.2% for those with a college education; p = 0.001). Among those with a history of HTN, only 56 (30.9%) had a normal presenting BP. Those with a history of HTN and normal ED presenting BP were no different from patients with elevated BP when comparing the in duration of HTN, medication compliance, location of usual follow-up care, and HTN-specific illness beliefs. CONCLUSIONS: In this single-center study, two out of every five Jamaican ED patients had elevated presenting BP, the majority of whom had a previous diagnosis of HTN. Among those with a history of HTN, 60% had an elevated presenting BP. The ED can be an important location to identify patients with chronic disease in need of greater disease-specific education. Further studies should evaluate if brief interventions provided by ED medical staff improve HTN control in this patient population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12245-018-0187-6) contains supplementary material, which is available to authorized users.